Wildlife Conflict, Integrative Conservation, and Coffee Farmers in Bener Meriah, Aceh: Sociological and Anthropological Perspectives - Fakhrurrazi, Fakhrurrazi; Yunanda, Rizki; Khairulyadi, Khairulyadi; Meliza, Richa; Yusniar, Yusniar (El-Usrah: Jurnal Hukum Keluarga, 2026)
Forest degradation has driven the emergence of the green economy as a paradigm of sustainable development. In Indonesia, the government strives to maintain forest conservation and food security simultaneously. However, human–wildlife conflict, such as that occurring in Bener Meriah Regency, Aceh, has become a huge challenge. Gayo coffee farmers face disturbances from elephants and tigers, which threaten both harvests and ecosystems. They respond to the challenges with local wisdom and integrative conservation approaches. Through the role of customary institutions and farmer groups and the potential of wildlife-friendly coffee, farmers have become key actors in sustainable and community-oriented conservation. In light of this, the present study employs a qualitative method using Antonio Gramsci’s critical sociology theory of hegemony and Clifford Geertz’s anthropological perspective of culture as a system of meaning. Data collection was carried out by means of observation, in-depth interviews, focus group discussions (FGD), and document analysis. The data analysis used was Spradley’s analysis technique consisting of domain analysis, taxonomic analysis, componential analysis, and thematic analysis. Findings reveal that the conflict between wildlife and coffee farmers in Bener Meriah has been caused by the loss of habitat and the expansion of plantation land. The conflict has fueled economic, social and cultural impacts. As such, the community has applied local wisdom as an adaptive strategy; yet, for sustainable solutions, it is necessary to have an integrative model, involving the government, conservation institutions and local communities.